Помогите упростить выражение с полным разбором, пожалуйста.

Помогите упростить выражение с полным разбором, пожалуйста.
Гость
Ответ(ы) на вопрос:
Гость
[latex] \frac{x^2+x\sqrt2}{x^2+2}\cdot \left (\frac{x}{x-\sqrt2}- \frac{\sqrt2}{x+\sqrt2} \right )= \frac{x(x+\sqrt2)}{x^2+2}\cdot \frac{x(x+\sqrt2)-\sqrt2(x-\sqrt2)}{(x-\sqrt2)(x+\sqrt2)} =\\\\= \frac{x(x+\sqrt2)}{x^2+2} \cdot \frac{x^2+x\sqrt2-x\sqrt2+2}{(x-\sqrt2)(x+\sqrt2)} = \frac{x\cdot (x+\sqrt2)(x^2+2)}{ (x^2+2)\cdot (x-\sqrt2)(x+\sqrt2)}= \frac{x}{x-\sqrt2} [/latex]
Не нашли ответ?
Ответить на вопрос
Похожие вопросы